NILAI-NILAI BUDAYA NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN DAN IMPLIKASINYA DALAM PEMBELAJARAN TEKS NOVEL - Indri Novitri; Abdurahman (EDU RESEARCH, 2024)
This research aims to identify the cultural values ​​contained in the novel Cantik Itu Luka by Eka Kurniawan and apply them in learning novel texts at the high school level. The method used is descriptive qualitative with a content analysis approach. The research results show that there are five main categories of cultural values ​​found in the novel, namely the relationship between humans and God, the relationship between humans and nature, the relationship between humans and society, the relationship between humans and others, and the relationship between humans and themselves. The cultural value of human relations with others is the most dominant, while the cultural value of human relations with God is found in smaller numbers. The implication of the results of this research is that the novel Cantik Itu Luka can be used as relevant open material to support student learning achievement, especially in analyzing cultural values ​​and building student character.